Sexual Activities and Changes in Condom Use in Group Sex Events Among Female Sex Workers in Melbourne, Australia - Lew, Chen; Fairley, Christopher K.; Tran, Julien; Phillips, Tiffany R.; Aung, Ei T.; Maddaford, Kate; Chen, Marcus Y.; Bradshaw, Catriona S.; Chow, Eric P. F. (Frontiers in Public Health, 2022)
Background There are few studies investigating group sex among female sex workers (FSWs). This study aimed to examine the typical number of group sex participants, sexual activities and condom use in group sex among FSWs attending a sexual health clinic in Melbourne, Australia. Methods We conducted a cross-sectional survey between May 1, 2019 and March 13, 2020 among FSWs in Melbourne. Participants were asked whether they had participated in group sex (sex involving more than two participants) within the past 3 months, the size of the most recent group sex event, sexual activities they engaged in and condom use. It is unknown whether this was a paid or unpaid event in our study. Results Of the 247 FSWs surveyed, the mean age was 28.9 years and 51.8% were born in Australia. More than a quarter (27.5%, n = 68) had had group sex in the past 3 months with the number of events ranging from 1 to 10 times. The median size of the group was 3 participants with one man and two women (including the FSW) being the most common combination. Kissing was the most common activity in group sex. Of 58 FSWs who had vaginal sex during group sex, 77.3% (51/58) reported their male partners always used condoms but 13.7% (7/51) of these did not change condoms between women. Conclusion This study finds that group sex is common among FSWs. Although condoms are always used during group sex, one in six men did not change their condoms between partners, which may increase STI transmission between partners.